The Genealogy of Authoritive Transmission of Sanad Al-Qur'an in Java Islamic Boarding Schools - Ahmad Jamil; Naswan Abdo Khaled (Universitas Darussalam Gontor, 2022)
Sanad is an important aspect of the Islamic scientific legacy in preserving science's legitimacy. Every Qur'an memorizer's dream is to have a sanad of the Qur'an. A unique lineage that lasted till the Prophet Muhammad SAW. This paper seeks to give an analysis of the importance and limitations of the sanad al-Qur'an diploma, as well as the role of Islamic boarding schools on the Indonesian island of Java in distributing the sanad al-Qur'an diploma. This study is a sort of field research that was carried out in Islamic boarding schools in Java. Method of descriptive analytic research. The findings of this study show that each pesantren (Islamic Boarding School) has its own procedure and technique for awarding the sanad al-Qur'an certificate. However, in general, the sanad al-Qur'an diploma will be awarded to santri and female students who have met the following criteria: memorizing the Qur'an 30 juz mutqin with correct recitation; depositing all of the memorization to the kiayi (listener); and having been declared to have passed the tasmi' 30 juz exam with certain conditions set by each pesantren. Based on the facts above, it is clear that the function of pesantren (Islamic Boarding School) is very significant in the transformation process of sanad certificates since pesantren has a unique environment and procedure for getting diplomas that cannot be obtained anywhere else. Furthermore, Islamic boarding schools play an important role in preserving the legitimacy of the Qur'anic sanad brought by Nusantara scholars until they are passed on to the Prophet.